Serum magnesium and copper levels in Bangladeshi women with gestational diabetes mellitus - Mishu, Farzana Akonjee; Muttalib, MA (IMC Journal of Medical Science, 2017)
Background and objectives: Alteration of magnesium (Mg) and copper (Cu) concentrations in blood has been observed in normal pregnancy as well as in gestational diabetes mellitus (GDM). The present study was aimed to evaluate the serum Mg and Cu levels in Bangladeshi women with GDM in their second and third trimester of pregnancy. Methods: The study was conducted at Mymensingh Medical College Hospital from July 2013 to June 2014. Pregnant women, in their second and third trimester, attending the outpatient department of Obstetrics and Gynecology and the Department of Endocrinology of Mymensingh Medical College Hospital were enrolled by purposive sampling technique. GDM was diagnosed on the basis of oral glucose tolerance test (OGTT) as defined in WHO criteria 2013. Blood glucose was estimated by enzymatic GOD-PAP colorimetric method. The cut off value for fasting plasma glucose level was ?6.1 mmol/L or ?7.8 mmol/L 2 hours after glucose load. Serum Cu was estimated by 3, 5-DiBr-PAESA method and Mg by Xylidyl Blue-I Method as per manufacturers instruction. Results: A total of 172 pregnant women in their second and third trimester were enrolled. Out of 172 participants, 86 had GDM and 86 were normoglycemic (control). The mean age of GDM and control groups was 28.6±3.2 years and 27.3±3.1 years respectively. The BMI was 26.4±1.5 m/kg2 and 26.3±1.3 m/kg2. Serum Mg level was significantly low (p< 0.001) in 2nd and 3rd trimesters in GDM cases (1.39±0.26 mg/dl and 0.93±0.15 mg/dl) compared to control group (1.67±0.3 mg/dl and 1.67±0.31mg/dl). On the contrary, serum Cu levels in GDM cases were significantly (p<0.002) higher in both trimesters (224±333.8 ?g/dl and 243.91±6.89 ?g/dl) compared to those without GDM (220.1±7.6 ?g/dl and 234.9±4.6 ?g/dl). There was significant (p<0.001) increase of serum Cu levels in 3rd trimester compared to 2nd trimester in both GDM and non GDM cases. Conclusion: There was distinct alteration of serum Mg and Cu levels in GDM compared to normal pregnancy. IMC J Med Sci 2017; 11(1): 25-28